IMPLEMENTING TASK – BASED LANGUAGE TEACHING ON CREATIVE TASK TO IMPROVE WRITING DESCRIPTIVE TEXTS - Prastiwi, Agnes Lusi Handaru; Salam, Urai; Sutapa, Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract The purpose of this research was to improve students’ writing descriptive texts  of the eighth grade at SMPN 3 Anjongan in Mempawah Regency. The researcher employed Jane Willis’ Task – Based Language Teaching (TBLT) framework which consisted of (1) Pre-task, (2) Task cylce and (3) Language focus. Moreover, the creative task which involved the authentic media that was tourist brochure energized the students enthusiastic in teaching learning process.The study results were derived from quantitative and qualitative data yielded from the action research designed. The result shown that the application of TBLT framework to teach writing descriptive through creative task (tourist brochure) could successfully improve students’ ability in writing. The findings also revealed that tourist brochure’s effective implementation required proper time management as well as sufficient teacher’s guidance during the writing process.   Keywords: Task – Based  Language Teaching, Writing Descriptive Text, Creative Task. Abstrak Tujuan dari penelitian ini adalah meningkatkan kemampuan menulis teks deskriptif pada peserta didik kelas delapan di SMPN 3 Anjongan di Kabupaten Mempawah. Peneliti melaksanakan kerangka Pembelajaran Bahasa Berbasis Tugas (TBLT) dari Jane Willis yang terdiri dari (1) Pre-task, (2) Siklus Task  and (3) Fokus Kebahasaan. Terlebih lagi, Tugas yang Kreatif melibatkan media otentitk berupa brosur wisata memicu antusiasme para peserta didik dalam proses pembelajaran. Hasil peneletian terdiri dari data kuantitatif dan data kualitatif pada penelitian tindakan kelas. Hasil penelitian menunjukkan bahwa aplikasi kerangka TBLT pada pengajaran menulis deskriptif melalui Kreatif Task (brosur wisata) dapat meningkatkan kemampuan menulis para peserta didik. Hasil penelitian juga menunjukkan bahwa implementasi brosur wisata efektif bila penggunaaan pengaturan waktu yang baik begitu pula bimbingan dari guru selama proses kegiatan menulis berlangsung. Kata kunci: Task – Based Language Teaching, menulis teks deskriptif, Tugas yang Kreatif